THE INFLUENCE OF GENDER ON READING COMPREHENSION - Ngongare, Gabriela; Samola, Nurmin F.; Rettob, Aloysius (Journal of English Language and Literature Teaching, 2023)
This study deals with the effect of gender differences on reading comprehension. The purpose is to answer the question: Does female students perform more significantly on reading comprehension of neutral text than do male students? The study that was conducted in the academic year 2019/2020, is pre-experimental in nature intact group design, and involved 60 grade students purposely selected based on their gender as the sample. They are then assigned into two treatment groups. The data are collected using an objective type test in multiple-choice format, and are analyzed statistically using t-test for independent sample. Result of the analysis showed that at p .05 and df 58, the t-observed is larger than t-table [3.333 ≥ 2.000). This indicates that female students outperformed their male counterparts in reading comprehension. In other words, it can be stated that gender differences affect reading comprehension